Designing a conceptual model for the climate change impact on agricultural performance and food security: a study based on farmers and policymakers’ experiences in the agricultural sector - Sifaei, Maryam; Saadollahi, Pouria (Frontiers in Food Science and Technology, 2025)
IntroductionThe present study aimed to design a conceptual model of the climate change impact on agricultural performance and food security, which focused on experiences of farmers and policymakers in the agricultural sector.MethodsIn terms of its purpose, it was an applied research and in terms of nature, it was a qualitative study using grounded theory technique. The statistical population consisted of all farmers in Kermanshah city, experts, university professors and policymakers. In this study, totally 18 individuals were investigated using a non-probability purposive sampling and snowball method until reaching theoretical saturation. An in-depth semi-structured individual interview was carried out for data collection and then MAXQDA 2018 software was applied for data coding. Thereafter, 18 major categories were identified in six grounded theory groups.ResultsAccording to the results, agricultural instability and food security threats were influenced by the causal factors as a result of climate change. These causal factors included severe climate change, reduced production capacity, economic instability of farmers, and dependence on natural resources. This issue is formed in a context of background conditions including climatic characteristics, agricultural infrastructure, prevailing policies, economic and social conditions, which is influenced with economic, social, technological, environmental, policy-making, and international constraints as the intervening factors. To address this challenge, strategies such as water resource management, crop optimization, support policies, education and extension, and social measures should be adopted to alleviate economic collapse, food security crisis, natural resource degradation, migration, social instability, and governance inefficiency.DiscussionIn conclusion, to reduce agricultural instability and food security threats, increasing agricultural system resilience to the climate change is suggested through developing new technologies, strengthening support policies, optimizing resource management, and educating farmers.